Relationality or Hospitality in Twenty-First Century Research? Big Data, Internet of Things, and the Resilience of Coloniality on Africa - Artwell Nhemachena; Nokuthula Hlabangane; Maria B Kaundjua (Modern Africa)
In a supposedly relational world, African people are increasingly datafied, dehumanised and denied self-knowledge, self-mastery, self-organization and data sovereignty. They are datafied, dehumanised and recolonised by foreign corporations and states engaged in the new scramble for African data. Arguing for more attention to data sovereignty, this article notes that the relational Internet of Things and Big Data threaten the autonomy, privacy, data, and national sovereignty of Africans. Deemed, in relational ontologies, to be lacking autonomy and to be indistinct from machines/nonhumans/animals, Africans would then be inserted or implanted with remotely controlled intelligent tracking devices that mine data from their brains, bodies, homes, cities and so on. Because technological relationality effaces distinctions between nature and culture, it legitimised mining data from human minds/bodies as if the data were natural minerals.